Analysis Of Microbial and Chemistry Contamination Thai Tea Drink in Junior High School - Titi Rohmayanti; Indiana Janet; Raden Siti Nurlaela (JURNAL AGROINDUSTRI HALAL, 2024)
Thai Tea drink is the current favorite drink of the current millennial generation. Thai Tea beverage products are usually sold in places that are easily accessible to consumers, such as on the side of the highway. This thing makes Thai Tea beverage products have potential to become a medium for foreign object to enter the body if they are not processed properly. This study aims to determine the safety of Thai Tea beverage products that are sold around junior high schools in Central Bogor District. This study used seven samples taken from 7 junior high schools in seven different sub-districts and used a purposive sampling method. Product analysis was carried out twice, including testing the microbial contamination levels of Total Plate Number, Coliforms, Escherichia coli, heavy metal lead chemical contamination and sucrose content in Thai Tea drinks. Research is also supported by field observations and interviews. The research showed that all samples of Thai Tea drinks contained TPC microbial contamination that exceeded the standard, twelve repetition were contaminated with coliform bacteria and Escherichia coli, all repetition were not detected by heavy metal lead contamination and the sucrose content of all repetition did not exceed the maximum daily sugar intake limit.